Development of cloud-based monitoring system for underground resistivity and soil measurement / Khairunnisa Nabilah Juhari ...[et al.] - Juhari, Khairunnisa Nabilah; Mohamed, Akmal Hafiz; Jusoh, Mohamad Huzaimy; Aziz, Norazam (UiTM Press, 2018)
Geo-electrical resistivity measurement is one of the established geophysical methods for evaluating the underground profile. It provides the detail of electrical resistivity under the ground which can be utilised to study various application in engineering, geology and environmental problems. This paper presents an approach to integrate a normal operating system of a resistivity meter and soil sensor with the cloud-based monitoring system. The conventional method used in the monitoring system is somehow not applicable to all operating devices such as the need to monitor real-time data that can be accessed over the internet. Thus, this project proposes the implementation of Internet of Things (IoT) development tools to develop data acquisition system (DAQ) for real-time underground resistivity and soil condition monitoring system. The system was developed using an open development board that is supported by OpenWrt Linux distribution which allows the user to fully customise the system. The real-time data can be monitored from the open source database platform where the data are displayed and stored. The development of this system has particularly improved the feasibility of data monitoring and thus shows the practicality of the developed system.